Memberantas Kejahatan Transnasional di Jalur Segitiga Asia Tenggara, Wilayah Perairan Laut Sulu - Rahman, Adi Fadhilah Nurul; Susiatiningsih, Rr. Hermini (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Sulu Sea is potential trade route in Southeast Asia region, located between Indonesia, Malaysia, and Phillipines. As the function for trading route, this sea possibly jeopardized by threats such as piracy. Data collection techniques used in this study are library research, and use qualitative method. This research utilized the concept of transnational crime by M. Cherif Bassioni for proving the transnational element in the occurring crime. Moreover, the concept of maritime security by Klein also has been implemented in order to fully protect the sovereign territory from existed threats in the sea. To realize it, this research applied Robert Keohane’s neo-liberal institutionalism theory for explaining Indonesia, Malaysia, and Phillipinnes struggles for their maritime security. Those countries had declared the broad cooperation among them to protect Sulu-Sulawesi. The cooperation generated several responsibilities to implement for the members and essentially required compliance of them. In addition, the three countries also conduct joint exercises and patrols. Furthermore, the cooperation had decreased significantly the number of piracy in that sea. This research also examined the supports and burdens which had been experienced by this vigorous cooperation. The results that obtained from this effort are a decrease in crime rates in the Sulu Sea waters.